Peningkatan Hasil Belajar Tingkat Tinggi Muatan Pembelajaran IPA Tema Selalu Berhemat Energi Melalui Pembelajaran Covid-19 Metode Blended Learning Pada Kelas IV UPTD SDN 01 Tanjuang Haro Sikabu-Kabu Pd. Panjang Semester Ganjil Tahun Pelajaran 2021/2022 - Ermiati Ermiati (Journal on Education, 2022)
The purpose of this study was to describe the use of blended learning method for covid-19 learning to improve students' high-level learning outcomes in science learning content in class IV UPTD SD Negeri 01 Tanjuang Haro. This type of research is Classroom Action Research. The research was carried out based on classroom action research steps with two cycles starting from the planning, implementation, observation and reflection stages. Data were obtained from the research subjects, namely teachers and students of class IV, totaling 19 people, which was held from July to July. September 2021. The results of the research data analysis show that the use of a scientific approach with the blended learning method can improve the ability of teachers in preparing high-level questions. This is evidenced by the acquisition of a score of 62.50 in the spracycle, increased to 72.91 in the first cycle, and increased to 89.58 in the second cycle. Furthermore, the results of the study of descriptions also increased, namely 61.53 in the pre-cycle, increasing to 76.92 in the first cycle of activities, and increasing to 87.71 in the second cycle. Furthermore, the learning outcomes of students' knowledge also increased, namely 69.15 in pre-cycle activities, increasing to 75.26 in the first cycle, increasing again to 84.21 in the second cycle with a large increase of 15.06. The learning outcomes of the skills aspect obtained an average of 62.94 in the pre-cycle, increasing to 71.94 in the first cycle and increasing again to 82.68 in the second cycle with a percentage increase of 19.74. Based on the results of this study, the conclusions of the research using the scientific approach of the blended learning method on the content of science learning need to be applied and developed in order to improve the quality of education.